2010
DOI: 10.1152/ajpendo.00356.2009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fat content on phospholipid fatty acid profile is muscle fiber type dependent

Abstract: IR has been linked to alterations and increased saturation in the phospholipid composition of skeletal muscles. We aimed to determine whether HFD feeding affects fatty acid (FA) membrane profile in a muscle fiber type-specific manner. We measured phospholipid FAs and expression of FA synthesis genes in oxidative soleus (SOL) and glycolytic extensor digitorum longus (EDL) muscles from rats fed either standard chow (standard laboratory diet, SLD) or a HFD. The HFD increased fat mass, plasma insulin, and leptin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 59 publications
(62 reference statements)
6
19
0
Order By: Relevance
“…Fatty acids are supplied to the fiber either by fatty acids bound to albumin or by hydrolyzed triacylglycerides [35]; they were converted to acyl CoA, and then finally to acylcarnitines to enter the mitochondrial where they can undergo ß oxidation [35]. In terms of phosphatidylcholines (PCs), most of the identified PCs showed localization and higher abundance in the oxidative region were composed of 18:1 (oleic) fatty acid tail; this observation is also in concordance with literatures [36, 37] that showed higher amount of oleic fatty acid as PC fatty acid tail in SOL. One explanation to this difference in PC fatty acid tail composition between oxidative and glycolytic regions is that there is a greater number of long-chain fatty acid transporters in oxidative muscles compared to glycolytic [38]; this difference in fatty acid transporter population also explains the differences in acycarnitine abundance between the two regions.…”
Section: Discussion and Summarysupporting
confidence: 77%
“…Fatty acids are supplied to the fiber either by fatty acids bound to albumin or by hydrolyzed triacylglycerides [35]; they were converted to acyl CoA, and then finally to acylcarnitines to enter the mitochondrial where they can undergo ß oxidation [35]. In terms of phosphatidylcholines (PCs), most of the identified PCs showed localization and higher abundance in the oxidative region were composed of 18:1 (oleic) fatty acid tail; this observation is also in concordance with literatures [36, 37] that showed higher amount of oleic fatty acid as PC fatty acid tail in SOL. One explanation to this difference in PC fatty acid tail composition between oxidative and glycolytic regions is that there is a greater number of long-chain fatty acid transporters in oxidative muscles compared to glycolytic [38]; this difference in fatty acid transporter population also explains the differences in acycarnitine abundance between the two regions.…”
Section: Discussion and Summarysupporting
confidence: 77%
“…A plausible hypothesis that arises from our investigation is that the lack of concordance between GM and LTL QTL maps might be partly explained by geneticfactors related with niRNA expression. Previous studies performed in rats indicated the existence of differences in the gene expression profiles of certain muscles types (Donsmark et al, 2002;Janovská et al, 2010). Moreover, transcriptomic analyses performed in pigs are closely aligned with these results.…”
Section: Lack Of Concordance Between Qtl Maps For CM and Ltl Muscles supporting
confidence: 76%
“…1C). A fiber-type-specific effect of HFD feeding on the intramyocellular lipid [33] and phospholipid FA content [34] in rodent muscles has been reported previously, showing accumulation in FT muscle (gastrocnemius [33] and EDL [34]) but not ST oxidative soleus muscle [33,34]. Changes in FA composition of FT EDL muscle largely reflected FA composition of the diets [17], suggesting storage of surplus dietary FAs in TAG.…”
Section: Impact Of Hfd Feeding On Skeletal Muscle Fa Metabolismsupporting
confidence: 62%